Squamous cell carcinoma admixed with sebaceous carcinoma of upper lip in a 7-year-old female - Katherine C. Benedict; Youssef Al Hmada; Catherine Gordon; Ian Hoppe (Elsevier, 2022)
Non-melanoma skin cancer in the pediatric population is an uncommon entity and its occurrence must prompt evaluation for underlying risk factors or genetic predisposition. We present a rare case of a 7-year-old female who presented with a rapidly growing, ulcerated, exophytic lesion to the philtrum of the cutaneous upper lip. She underwent wide local excision with intra-operative frozen sections, final pathology showed moderately differentiated squamous cell carcinoma with a 15-20% component of sebaceous carcinoma. She has subsequently been evaluated by genetics with no identifiable predisposing condition and remains free from recurrence.